Nonlinear analysis of circular double-skin concrete-filled steel tubular columns under axial compression. (15th January 2017) - Liang, Qing Quan
Highlights: A new numerical model for simulating circular DCFST short columns is developed. New material laws for sandwiched concrete in DCFST columns are described. Parametric study on DCFST columns is conducted using the verified numerical model. The numerical and design models developed are shown to yield accurate predictions. Abstract: The use of the circular hollow steel tube in a circular concrete-filled steel tubular (CFST) column significantly alters the confinement mechanism in the conventional CFST column. The confinement models proposed for conventional circular CFST columns are therefore not applicable to circular double-skin CFST (DCFST) columns. This paper presents a new numerical model for predicting the structural performance of circular DCFST short columns under axial compression. The numerical model incorporates new material constitutive relationships of sandwiched concrete in circular DCFST columns. The confinement effects provided by the outer and inner steel tubes on the sandwiched concrete in circular DCFST columns are taken into account in the numerical formulations. Comparisons with existing experimental results on circular DCFST short columns are made to verify the numerical model developed. The numerical model is used to undertake parametric studies to examine the effects of important geometric and material parameters on the strength and ductility of axially loaded DCFST short columns. It is demonstrated that the numerical model can accurately capture the complete axial load-strain characteristics of circular DCFST short columns under axial compression. A design formula is proposed and found to predict well the ultimate axial loads of circular DCFST short columns.